Illegal parking and its implications for MSMEs in Yogyakarta: An information literacy perspective - Andriyana Fatmawati; Haris Ahmad Daffa (Jurnal Penelitian Humaniora, 2026)
The growth of MSMEs in Yogyakarta faces significant challenges due to the prevalence of illegal parking, which disrupts public order, urban aesthetics, and consumer accessibility. This study aims to explore the implications of illegal parking on MSMEs from an information literacy perspective and to develop an information literacy integration model to address these issues. This study employs a qualitative method with a case study approach. Six MSME actors in Yogyakarta were selected as informants. Data were collected through observation, documentation, and semi-structured interviews, and analyzed using an interactive analysis model. The researcher acted as the primary instrument, supported by an interview guide. The findings indicate that illegal parking significantly reduces customer accessibility and leads to a decline in business revenue. In addition to economic impacts, illegal parking contributes to social conflict and deteriorates the image of the area. Information literacy emerges as a key element that enables business actors to understand regulations, evaluate credible information, and engage in data-driven advocacy with local government. As a sustainable solution, this study proposes a three-phase integration model consisting of a capacity-building phase, a solution implementation phase, and a sustainability phase. The implementation of this model is projected to enhance local government revenue, mitigate social conflict, and foster a more conducive business ecosystem through active collaboration between business actors and government institutions.